Associations between congenital heart defects and genetic and morphological anomalies. The importance of prenatal screening - Pavlíček, Jan; Gruszka, Tomáš; Kaprálová, Sabina; Procházka, Martin; Šilhánová, Eva; Kaniová, Romana; Polanská, Slávka; Černičková, Renáta; Klásková, Eva (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2019)
AIM: To study congenital heart defects (CHDs), evaluate their relation to extra-cardiac pathologies, and assess the significance of prenatal diagnostics for heart diseases. METHODS: Data from 1999-2017 were analyzed for the incidence of significant CHDs in fetuses (prenatal ultrasound/echocardiography) and children, including, where applicable, autopsy data and genetic evaluation. RESULTS: Among 220,400 fetuses, 819 (3.7 cases per 1000) significant CHDs were observed. Of the total, 53% (435/819) of CHDs were diagnosed prenatally. The heart defect was an isolated impairment in 78% (640/819), associated with a genetic impairment in 16% (128/819), and with extra-cardiac malformations without genetic pathology in 6% (51/819). Chromosomal aberrations were diagnosed prenatally in 70% (90/128) of those affected and extra-cardiac conditions in 86% (44/51). The CHD and genetic pathology association was more frequent prenatally [21% (90/435) vs. postnatally: 10% (38/384; P<0.0001)], as was the association between CHD with other extra-cardiac pathology and a normal karyotype [prenatally: 10% (44/435) vs. postnatally: 2% (7/384; P<0.0001)]. CONCLUSION: Heart defects are most frequently isolated, with genetic and other extra-cardiac anomalies in about one third of cases, significantly linked to prenatal diagnostics.
Keywords: gestační stáří; echokardiografie; Female; pitva; novorozenec; Gestational Age; Heart Defects, Congenital; ženské pohlaví; prenatální diagnóza; lidé; Infant, Newborn; Pregnancy Outcome; těhotenství; Prenatal Diagnosis; Echocardiography; Incidence; Ultrasonography, Prenatal; retrospektivní studie; incidence; chromozomální aberace; výsledek těhotenství; vrozené srdeční vady; Autopsy; Pregnancy; ultrasonografie prenatální; Retrospective Studies; Chromosome Aberrations; Humans